Nanomaterial Based Biosensors for Detection of Viruses Including SARS-CoV-2: A Review - Bisht, Ayushi; Mishra, Abhishek; Bisht, Harender; Tripathi, R. M. (Journal of analysis and testing, 2021)
The COVID-19 outbreak led to an uncontrollable situation and was later declared a global pandemic. RT-PCR is one of the reliable methods for the detection of COVID-19, but it requires transporting samples to sophisticated laboratories and takes a significant amount of time to amplify the viral genome. Therefore, there is an urgent need for a large-scale, rapid, specific, and portable detection kit. Nowadays nanomaterials-based detection technology has been developed and it showed advancement over the conventional methods in selectivity and sensitivity. This review aims at summarising some of the most promising nanomaterial-based sensing technologies for detecting SARS-CoV-2. Nanomaterials possess unique physical, chemical, electrical and optical properties, which can be exploited for the application in biosensors. Furthermore, nanomaterials work on the same scale as biological processes and can be easily functionalized with substrates of interest. These devices do not require extraordinary sophistication and are suitable for use by common individuals without high-tech laboratories. Electrochemical and colorimetric methods similar to glucometer and pregnancy test kits are discussed and reviewed as potential diagnostic devices for COVID-19. Other devices working on the principle of immune response and microarrays are also discussed as possible candidates. Nanomaterials such as metal nanoparticles, graphene, quantum dots, and CNTs enhance the limit of detection and accuracy of the biosensors to give spontaneous results. The challenges of industrial-scale production of these devices are also discussed. If mass production is successfully developed, these sensors can ramp up the testing to provide the accurate number of people affected by the virus, which is extremely critical in today’s scenario.